On the Process of Borrowing: A Comparative Analysis of the Use of ‘Monitoring’ in Russian and Polish - Luciński, Kazimierz (Respectus Philologicus, 2014)
This paper focuses on the word monitoring (RU: мониторинг, PL: monitoring), borrowed into both Russian and Polish from English and widely used today. In the author’s opinion, this word reflects one of the key notions of modern reality, that of applying technical means to enable the observation of both material objects and social processes along with their subjects. The meaning of the word мониторинг in the Russian language is not equivalent to the meanings of words commonly considered its synonyms (e.g., observation, control, forecast, and evaluation). Unlike these other Russian words, мониторинг implies an idea of active influence on the running processes and, in this sense, points to a new notion in Russian culture. Thus, it cannot be concluded that the use of this loanword has superseded native Russian words. The author concentrates on several differences related to this word in the compared languages. In the Polish language, the word monitoring means “a continuous observation and control of processes,” and is used in discourses that advertise security and bodyguard services, whereas in the Russian language, this word is more frequently used in discourses related to the observation of social processes and is connected to the idea of metaphorical tracking.